Parental Hostility as a Moderator of the Criminogenic Effect of Parental Criminal Justice Contact Among Youth Adjudicated of Serious Offenses - Chlebuch, Natasha (Criminal justice and behavior, 2025)
Evidence suggests that having justice-involved parents increases the odds of juvenile offending, including serious delinquency. Recent research has shifted focus to precipitating risk/protective factors that may moderate the link between parental offending and delinquency, including the parent−adolescent relationship. This study aimed to investigate whether the affective relationship with a parent attenuates the effect of criminogenic transmission, as demonstrated by fewer types of offending behaviors among a sample of youth adjudicated of serious offenses whose parents have had prior criminal justice contact. A significant interaction between paternal and maternal justice involvement and maternal and paternal hostility was found for males, but not for females, such that the criminogenic effect of parental justice involvement is slightly weakened for justice-involved males whose relationship with their mother and father is characterized by relatively high rates of hostility.